The Integration of Financial Literacy, Financial Attitude, and Financial Motivation in Shaping Sharia Compliant Financial Management Behavior - Rosilawati, Weny; Aisyah Balqis; Maya Meilia (Al-Mashrof: Islamic Banking and Finance, 2025)
This study examines the effects of financial literacy, financial attitude, and financial motivation on financial management behavior among residents of Sukarame District, Bandar Lampung, from an Islamic economic perspective. A quantitative approach was applied using survey data collected from 100 respondents selected through purposive sampling. The data were analyzed using PLS-SEM with SmartPLS 4. The findings reveal that financial literacy, financial attitude, and financial motivation each have a positive and significant influence on financial management behavior. From an Islamic perspective, these behaviors reflect the principles of trustworthiness (amanah), moderation, transparency, and social responsibility, as emphasized in Sharia teachings.This study contributes to the literature on Islamic financial behavior by integrating cognitive, psychological, and motivational dimensions into a unified sharia-based behavioral framework, providing both theoretical enrichment and practical implications for Islamic financial education and policy. Keywords: Financial Literacy; Financial Attitude; Financial Motivation; Financial Management Behavior; Islamic Economics.